DNA-mediated immunization to the hepatitis B surface antigen in mice: aspects of the humoral response mimic hepatitis B viral infection in humans. - Michel, M L (1995)
Intramuscular injection of plasmid DNA expression vectors encoding the three envelope proteins of the hepatitis B virus (HBV) induced humoral responses in C57BL/6 mice specific to several antigenic determinants of the viral envelope. The first antibodies appeared within 1-2 weeks after injection of DNA and included antibodies of the IgM isotype. Over the next few weeks, an IgM to IgG class switch occurred, indicating helper T-lymphocyte activity. Peak IgG titers were reached by 4-8 weeks after a single DNA injection and were maintained for at least 6 months without further DNA injections. The antibodies to the envelope proteins reacted with group- and subtype-specific antigenic determinants of the HBV surface antigen (HBsAg). Expression vectors encoding the major (S) and middle (preS2 plus S) envelope proteins induced antibodies specific to the S protein and preS2 domain, and preS2 antibodies were prominent at early time points. In general, the expression vectors induced humoral responses in mice that mimic those observed in humans during the course of natural HBV infection.